Higher Education as a Bridge between China and Nepal: Mapping Education as Soft Power in Chinese Foreign Policy - Gauttam, Priya; Singh, Bawa; Chattu, Vijay Kumar (Societies, 2021)
In this globalized world, education has become an important medium to enhance people-to-people contact. The Delores report of the International Commission on Education for the 21st century highlights the enormous potential of higher education to use globalization as a resource for bridging the knowledge gap and enriching cross-cultural dialogue. As a major contributor to soft power and an important field of public diplomacy, international education can have a wealth of advantages, including the ability to generate commercial value, promote a country’s foreign policy goals and interests, and contribute to economic growth and investment. The People’s Republic of China, well-known for being the world’s most populous nation and the global economic powerhouse, prioritizes the internationalization of the country’s higher education system. China is looking to expand its higher education program and carry out its diplomatic project in South Asia. In this sense, the South Asian zone, especially Nepal, is significant for China, where its educational diplomacy is playing as a “bridge between Sino- Nepal relations.” In this review, we describe the place and priority of “Education” in China’s foreign policy; explore China’s mediums of investment in Nepal’s education sector; and highlight the importance of educational aid in Sino-Nepal relations. Chinese educational aid to Nepal takes many forms, where Nepali students and officials engage with Chinese investment to enhance their career prospects and the education system in Nepal
Keywords: Education; Sino-Nepal relations; Public diplomacy; Soft power; Educational aid; Investment; Asian societies; Belt and Road Initiative (BRI); Geopolitical